Towards a standardised cross-sectoral data access agreement template for research: a core set of principles for data access within trusted research environments - Brophy, Rachel; Bellavia, Ester; Groot Bluemink, Maeve; Evans, Katharine; Hashimi, Munisa; Macaulay, Yemi; McNamara, Edel; Noble, Allison; Quattroni, Paola; Rudczenko, Amanda; Morris, Andrew D; Smith, Cassie; et al. (International Journal of Population Data Science, 2023)
Introduction Trusted Research Environments (TREs) are secure computing environments that provide access to data for approved researchers to use in studies that can save and improve lives. TREs rely on Data Access Agreements (DAAs) to bind researchers and their organisations to the terms and conditions of accessing the infrastructure and data use. However, DAAs can be overly lengthy, complex, and can contain outdated terms from historical data sharing agreements for physical exchange of data. This is often cited as a cause of significant delays to legal review and research projects starting. Objectives The aim was to develop a standardised DAA optimised for data science in TREs across the UK and framed around the `Five Safes framework' for trustworthy data use. The DAA is underpinned by principles of data access in TREs, the development of which is described in this paper. Methods The Pan-UK Data Governance Steering Group of the UK Health Data Research Alliance led the development of a core set of data access principles. This was informed by a benchmarking exercise of DAAs used by established TREs and consultation with public members and stakeholders. Results We have defined a core set of principles for TRE data access that can be mapped to a common set of DAA terms for UK-based TREs. Flexibility will be ensured by including terms specific to TREs or specific data/data owners in customisable annexes. Public views obtained through public involvement and engagement (PIE) activities are also reported. Conclusions These principles provide the foundation for a standardised UK TRE DAA template, designed to support the growing ecosystem of TREs. By providing a familiar structure and terms, this template aims to build trust among data owners and the UK public and to provide clarity to researchers on their obligations to protect the data. Widespread adoption is intended to accelerate health data research by enabling faster approval of projects, ultimately enabling more timely and effective research.